2006
DOI: 10.1177/1534735406291499
|View full text |Cite
|
Sign up to set email alerts
|

Preadministration of High-Dose Salicylates, Suppressors of NF-κB Activation, May Increase the Chemosensitivity of Many Cancers: An Example of Proapoptotic Signal Modulation Therapy

Abstract: NF-κB activity is elevated in a high proportion of cancers, particularly advanced cancers that have been treated previously. Cytotoxic treatment selects for such up-regulation inasmuch as NF-κB promotes transcription of a large number of proteins that inhibit both the intrinsic and extrinsic pathways of apoptosis; NF-κB also boosts expression of mdr1, which expels many drugs from cells. Indeed, high NF-κB activity appears to be largely responsible for the chemo-and radioresistance of many cancers. Thus, agents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(51 citation statements)
references
References 269 publications
3
46
0
2
Order By: Relevance
“…Likewise, HDI-induced cell death can be augmented by inhibiting the antiapoptotic transcription factor NF-κB (24,25), whose activation is blocked by aspirin and salicylic acid (26,27). It is currently under discussion that salicylates and other NSAIDs in general may have synergistic efficacy when combined with anticancer agents (28,29). However, there are also a number of studies that suggest otherwise.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, HDI-induced cell death can be augmented by inhibiting the antiapoptotic transcription factor NF-κB (24,25), whose activation is blocked by aspirin and salicylic acid (26,27). It is currently under discussion that salicylates and other NSAIDs in general may have synergistic efficacy when combined with anticancer agents (28,29). However, there are also a number of studies that suggest otherwise.…”
Section: Discussionmentioning
confidence: 99%
“…However, at higher concentrations, aspirin has also been shown to block NF-kB activity by directly binding to and inhibiting the kinase activity of IKKb by reducing its ability to bind ATP (Yin et al, 1998); more recently, aspirin has also been reported to inhibit proteasome activity and consequently to interfere with degradation of IkB (Dikshit et al, 2006). As such, high-dose aspirin therapy may have applications to diseases where NF-kB activity is involved, including cancer (McCarty and Block, 2006), diabetes (Yuan et al, 2001) and heart disease (Li and Fang, 2004).…”
Section: Anti-inflammatory Drugsmentioning
confidence: 99%
“…143 The possible utility of high-dose aspirin in cachexia prevention is of particular interest in light of the fact that this drug, via joint inhibition of NF-κB and both cox isoforms, may have potential for inhibiting the malignant behavior of many cancers while increasing their apoptotic responsiveness to cytotoxic therapy and slowing angiogenesis. 144 The possibility that silymarin and TTM might also influence cachexia via NF-κB modulation is worthy of consideration, although it is unclear whether these agents affect NF-κB in skeletal muscle.…”
Section: Preventing Cachexiamentioning
confidence: 99%